International economic law - Lowenfeld, Andreas F. (Oxford University Press, 2008)
The book covers all the major elements of economic law in the international arena including the World Trade Organization and its antecedents; dumping, subsidies, and other devices that alter the market; the International Monetary System, including the collapse of the Bretton Woods system; the debt of developing countries; the law of foreign direct investment, including changing perceptions of the rights of host states and multinational enterprises; and economic sanctions. The book also contains chapters on competition law, environmental law, and new chapters on intellectual property and the various forms of arbitration; demonstrating how these subjects fit into the framework of international economic law.